ANALISIS PENGARUH INDEKS HARGA SAHAM DI BURSA GLOBAL TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BEI - Ruth Christa; Wahyu Ario Pratomo (Ekonomi dan Keuangan, 2013)
This research aims to analyze the effect of the global stock price index against IDX Composite Index as well as to determine the proportion of the global stock price index influence either simultaneously or partially. The global stock price index that is used consists of five indices, namely the Dow Jones Industrial Average (USA), FTSE 100 (UK), Nikkei 225 (Japan), Shanghai Stock Exchange Composite (China), and the Hang Seng Index (Hong Kong). The data used are secondary data, which include the fluctuation of Composite Stock Price Index at BEI and the global stock price index for 48 months ( January 2008-December 2011). The analysis model used in this research is Path Analysis. Based on this research during the period January 2008-December 2011 the global stock price index has a significant simultaneous effect on IDX Composite Stock Price Index. Partially out of five global stock price index that is used there are three that have a significant influence, namely Dow Jones Industrial Average (49.7143%), Nikkei 225 (0.9308%) and Hang Seng (38.2936%).Keywords: Dow Jones Industrial Average Index, FTSE 100 Index, Nikkei 225 Index, Shanghai Stock Exchange Composite Index, Hang Seng Index, and IDX Composite Stock Price Index.